Work stress and burnout among licensed lawyers at Thai Lawyers Council under Royal Patronage. - Sh.Therdthoonphuphuch , W.; Lueboonthavatchai, P. (Chulalongkorn Medical Journal, 2023)
Background : Work Stress (occupational/job stress) is a psychological problem that seems increasing among lawyers in various countries nowadays due to organizational pressure for high performance that exceeds workloads or low job decision. The long-term work stress causes burnout that will reduce personal performance effectiveness. Work stress and burnout among licensed lawyers have not been studied in Thailand. Objectives : To identify the prevalence of work stress (occupational/job stress) and burnout, and the associated factors with work stress (occupational/job stress) and burnout among licensed lawyers of Thai Lawyers Council under Royal Patronage. Methods : Four hundred licensed lawyers were recruited at the Thai Lawyers Council under Royal Patronage from August 2015 to January 2016. All subjects completed four questionnaires include: 1) Personal data form; 2) Work information questionnaire; 3) Thai version of the Karasek’s Job Content Questionnaire with 45 items (Thai JCQ-45); and, 4) Thai version of Maslach Burnout Inventory with 22 items (Thai MBI 22). The associated factors of work stress and burnout were analyzed by chi-square test. Logistic regression was used to identify the predictors of work stress (occupational/ job stress) and burnout in licensed lawyers. Chi-square test was used to analyze the association between occupational stress and burnout. Results : The prevalence of work stress among licensed lawyers was 22.3% (89 subjects) and burnout 7.0% (28 subjects). Logistic regression showed that the predictors of work stress were average income above 40,000 baht and new and 2-year type of lawyer licenses (P < 0.01), and those with burnout were average income above 40,000 baht, work experience that was less than 10 years (P < 0.01), regular practice on legal advice on criminal cases and working hours less than or equal 8 hours per day (P < 0.05). Chi-square test showed that occupational stress was associated to burnout. Conclusion : In all 22.3% (89 persons) of licensed were considered work stress. The work stress lawyers were ones with new licenses or 2-year licenses to practice law, and had average income more than 40,000 THB per month; 7.0% (28 persons) of lawyers were considered burnout. The burnout lawyers were those with average income above 40,000 THB per month, and had work experiences less than or equal 10 years who were practicing legal advice on criminal cases and with working hours less than or equal 8 hours per day. The occupational stress was associated to burnout occurrence.